The Baby's Bouquet: A Fresh Bunch of Rhymes and Tunes - Crane, Walter, 1845-1915; Crane, Lucy, 1842-1882; Evans, Edmund, 1826-1905 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Baby's Bouquet: A Fresh Bunch of Rhymes and Tunes" by Walter Crane is a charming collection of nursery rhymes and musical pieces intended for children, produced during the late 19th century. This delightful work serves as a companion to Crane's earlier collection, "Baby's Opera," showcasing a variety of familiar rhymes and tunes that engage young readers and listeners. The book is characterized by its colorful illustrations and musical arrangements, aiming to introduce classic children's songs and stories to a new generation. The book features a compilation of popular nursery rhymes such as "Hot Cross Buns," "Polly Put the Kettle On," and "London Bridge," among many others. Each rhyme is accompanied by musical notation, making it easy for parents and caregivers to sing along with their children. The whimsical illustrations complement the lighthearted, playful nature of the verses, bringing the stories to life. Overall, "The Baby's Bouquet" is an enchanting celebration of childhood, inviting readers into a magical world of song and story, ensuring that these timeless pieces remain a joyful part of early childhood experiences. (This is an automatically generated summary.)
Release date is 2008-05-11
E-text prepared by Chris Curnow, Lindy Walsh, Linda Cantoni, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Nursery rhymes; Children's songs